"Impact of Institutional Changes Felt by Faculty Members": A Study with Reference to Management Institutes in Pune City. (June 2014) - Apte, Anand
Management Institutes are changing over the last decade because of competition, changes in technology, teaching pedagogy, and placement expectations from students and value for money for their parents. The next decade will bring even greater change impacting on all facets of the management institutes including major changes in infrastructure facilities, role of director, faculty members, and students of the management institutes. Changes may take place because of placement of students, faculty member's attitude toward students and institute etc. It is up to the management of the institute to see how effectively and smoothly these changes could be done to face competition. In this research paper an attempt has been made to know the need and types of changes required, effect of changes on faculty members and management institutes, and understanding and solving the difficulties in implementing changes in the management institutes. For this research paper 60 faculty members were covered from management institutes in Pune. It is a descriptive research and convenience sampling was used. Primary data were collected from questionnaires. Secondary data were collected from journals, magazines, and web sites. Data analysis and hypothesis testing were done. The study revealed that faculty members like the changes made by the institute, changes are due to less admissions and adopting new technology/methodology. Difficulties/problems for implementing the changes are: Barriers in communication, interpersonal relationship, no role clarity, not understanding the necessity for change, and not accepting responsibility for change.